A cooperação como instrumento de enfrentamento do real: o caso dos magistrados do trabalho no Brasil - Ruri Giannini; Laerte Idal Sznelwar; Seiji Uchida; Selma Lancman (Universidade do Porto, 2019)
Cooperation is a fundamental part of the construction of the workers' mental health and an essential pillar for building a work environment where there are trust at work. The objective of this paper is debating the formal and the informal cooperation networks which exist in the work of labor judges and the impacts they exert in facing the real work. Although the formal evaluation methods of judges are basically quantitative and individualist and there are no institutional mechanisms which reinforce the peer-to-peer exchanges and value the return of experience, we can observe the creation of cooperation networks within peers. This paper is part of the research "Constructing intersectorality in the field of occupational health: Perspective of Professionals in the Services Network of the City of São Paulo", sponsored by FAPESP. The methodology is based on the concepts of Psychodynamics of Work.